Pengaruh Gaya Kepemimpinan, Budaya Organisasi, Dan Motivasi Kerja terhadap Loyalitas Karyawan CV. Logam Jaya Abadi - Putra Geovani Koroh; Didik Subiyanto; Epsilandri Septyarini (Universitas Batanghari, 2023)
This study aims to analyze whether leadership style, organizational culture and work motivation can affect employee loyalty carried out at CV. Logam Jaya Abadi, Bitung City, North Sulawesi. This research is a survey research using the technique of distributing questionnaires to employees of CV. Metal Jaya Abadi which is the sample in the study. The determination of the sample is based on the Cohen Manion and Marriso table, with a confidence level of 90 per count by taking the least sample, which is close to 50. The hypothesis testing uses the t test and f test. The data testing technique in this study consisted of validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, t test, f test and coefficient of determination test. This study provides results that leadership style and organizational culture have a positive and significant effect on employee loyalty. However, work motivation gives negative results or does not affect employee loyalty, in research conducted in the field, researchers conclude that there are several factors such as salaries that are deemed inappropriate and inadequate health and old age benefits, which is why the work motivation variable is negative.